Galia Muskmelons: Evaluation for Florida Greenhouse Production - Elizabeth M. Lamb; Nicole L. Shaw; Daniel J. Cantliffe (EDIS, 2003)
Galia muskmelon (Cucumis melo Reticulatus group L.) is a specialty melon with green flesh and a golden-yellow netted rind, prized for its bold aroma and high sugar content. This document is HS919, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: May 2003.